Macrolophus pygmaeus (Rambur) as an efficient predator of the tomato leafminer Tuta absoluta (Meyrick) in Europe. A review - De Backer, L.; Caparros Megido, R.; Haubruge, E.; Verheggen, FJ. (Biotechnologie, Agronomie, Société et Environnement, 2014)
The tomato leafminer, Tuta absoluta (Meyrick), originates from South America, and remains one of the main tomato pests in this continent. Since its introduction to Europe in 2006, Mediterranean countries have also been exposed to this pest. Because of the endophytic habits of the larvae and ability of adults to reproduce parthenogenetically, chemicals and sexual pheromone-based control methods generate poor results. Recently, the use of biocontrol agents, such as Macrolophus pygmaeus Rambur (Heteroptera: Miridae), has been investigated as an alternative means of control, the results of which are presented in this review. Macrolophus pygmaeus is a mirid bug that is widely used to control different phytophagous insects in integrated pest management strategies through Europe. Several studies have confirmed the high predation potential of M. pygmaeus on T. absoluta under laboratory and semi-field conditions. This predator spontaneously colonizes tomato greenhouses in the southern Mediterranean countries. The use of banker plants (i.e., plants that provide a habitat to the predator) improves the colonization ability of this natural enemy. Hence, if the local population size is low, an augmentative strategy could be adopted. Predators may be released before or after the onset of pest infestation, with recommendations varying depending on natural population densities of both the pest and predator. The efficiency of M. pygmaeus has also been evaluated when used in combination with other biocontrol agents or with chemicals. This work presents an overview of different types of control strategies using M. pygmaeus against the tomato leafminer, T. absoluta.